Parabolic Nonlinear Second Order Slip Reynolds Equation: Approximation and Existence - Ait Hadi, K. (Nonlinear Analysis: Modelling and Control, 2007)
This work studies an initial boundary value problem for nonlinear degenerate parabolic equation issued from a lubrication slip model. Existence of solutions is established through a semi discrete scheme approximation combined with some a priori estimates.
Keywords: nonlinear parabolic boundary value problem; semi-discrete scheme; a priori estimates